Механічна обробка покриттів на етапі становлення відновлювальної техніки газотермічного напилення - Полонський, Л.Г. (Питання історії науки і техніки, 2007)
Показаны пути становления механической обработки напыленных газотермических покрытий и ее влияние на развитие ремонтного производства в ведущих индустриальных странах мира, в т.ч. в бывшем СССР и Украине. Ways of becoming of machining raised dust gas-thermal coverings and its influence on
development of repair manufacture in the leading industrial countries of the world, including
in the former USSR and Ukraine are shown.